The Analysis of the Relationship Between Prolanis Activities and Referral Diagnoses of Diabetes and Hypertension - Priscillia Josina Yacomina Antou; Margaretha Solang; Sunarto Kadir (Indonesian Journal of Global Health Research, 2026)
Hypertension and Diabetes Mellitus (DM) are leading causes of global mortality with continually rising incidences, impacting individuals' quality of life and imposing a significant burden on the healthcare system due to the high frequency of referrals to Advanced Level Health Facilities. The Chronic Disease Management Program (Prolanis) was initiated to address this issue by increasing awareness, adherence, and preventive activities through education and routine monitoring, which is expected to reduce referrals. This cross-sectional study aimed to analyze the relationship between participation in Prolanis activities and the referral of DM and Hypertension patients to Toto Kabila Regional General Hospital. The study sample involved 99 respondents who were DM and Hypertension patients registered as Prolanis participants and had been referred to the hospital, selected using an accidental sampling technique. Data were collected through a Prolanis participation questionnaire and secondary data from medical records for referrals. All instruments demonstrated acceptable psychometric properties, with significance values below 0.05 and Cronbach’s alpha coefficients exceeding 0.70. The analysis utilized the Chi-Square test and logistic regression. The statistical results indicate a highly significant relationship between patient referrals and participation in various Prolanis activities, including medical consultation (p = 0.002), reminders (p = 0.000), health status monitoring (p = 0.004), patient visits (p = 0.012), and Prolanis exercise (p = 0.000). The variable of Prolanis exercise had the greatest influence in reducing referrals, with an Odds Ratio of 5.37. Conclusion: Active participation in Prolanis activities, particularly physical activity, is strongly associated with a reduction in DM and Hypertension patient referrals. Health facilities are advised to prioritize and strengthen routine physical activities such as Prolanis exercise as the core of the program, while also improving the intensity and quality of reminder and monitoring activities to maximize patient adherence and the effectiveness of referral prevention.